2012
DOI: 10.1177/0363546512447792
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Medial Meniscus Posterior Root Tear

Abstract: 1Background: Medial meniscus posterior root tear (MMPRT) have a different

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
169
3
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(195 citation statements)
references
References 24 publications
8
169
3
9
Order By: Relevance
“…Their findings are in agreement with a cross-sectional aspect of the present loss of the structure that most robustly holds the meniscus in the normal anatomic position (2). Risk factors for meniscal root tears include female sex, high BMI, greater varus mechanical axis angle, and low levels of exercise (21). This entity seems to be more common than previously thought, with a frequency rate of around 10% (722 of 7148) in patients undergoing knee arthroscopy (22).…”
Section: Resultssupporting
confidence: 84%
“…Their findings are in agreement with a cross-sectional aspect of the present loss of the structure that most robustly holds the meniscus in the normal anatomic position (2). Risk factors for meniscal root tears include female sex, high BMI, greater varus mechanical axis angle, and low levels of exercise (21). This entity seems to be more common than previously thought, with a frequency rate of around 10% (722 of 7148) in patients undergoing knee arthroscopy (22).…”
Section: Resultssupporting
confidence: 84%
“…They concluded from their clinical findings that arthritis in the medial compartment is closely linked to the development of MMPRT. Hwang et al20) reported that the risk of MMPRT was higher by 5.9 times in females than males, 4.9 times if body mass index was more than 30 kg/m 2 , 3.3 times in knees with a varus mechanical axis, and 2.7 times in patients with a lower level of sports activities.…”
Section: Clinical Characteristics Of Mmprtmentioning
confidence: 99%
“…1,2 Meniscus root tears can occur in both acute and chronic settings, with the posterior meniscus roots being most commonly affected. [3][4][5] Whereas posterior lateral meniscus root tears are usually associated with acute tears of the anterior cruciate ligament in young male patients, 6,7 posterior medial meniscus root tears (PMMRTs) are mainly the result of degenerative meniscal disease in middle-aged women 8,9 (Fig 1A).…”
mentioning
confidence: 99%